Synchronicity analysis of meteorological variables on agricultural drought in the Loess Plateau, China - Fang Liu; Hongbo Zhang; Yihang Li; Zhiyuan Ning; Shuai Hao (Journal of Hydrology: Regional Studies)
Study region: This study focuses on the Wuding River Basin, located in the middle reaches of the Yellow River Basin in China. Study focus: Event Synchronization (ES) and Event Coincidence Analysis (ECA) were used to investigate the spatiotemporal co-evolution of the multi type of meteorological variable drought (SIMVs) and SSMI in the basin, including the precursor and triggering effect of SIMVs on agricultural drought and the occurrence and development of different levels of agricultural drought events under meteorological variable disturbance. New hydrological insights for the region: In the precursor-and-trigger analysis of ECA, SWI was the main precursor and trigger factor for mild agricultural drought and SPI for moderate and severe drought. The precursor coincidence rate is higher than the trigger coincidence rate, suggesting that not all precursory SIMV events cause agricultural drought. All precursory and triggering effects diminish as the observation time window rises, demonstrating that SIMV has a bigger impact on low-grade agricultural drought. SPI caused 26.86 % of agricultural drought, whereas coupled SIMVs triggered it. The synchronization analysis shows that the lag times for SPI, STI, SWI, and SNR early warnings of drought are 65.7 days, 60.5 days, 52.8 days, and 55.8 days, respectively. The lag times for SIMV triggers are 61.8 days, 53.7 days, 48.4 days, and 53 days.